Fire risk vulnerability and safety assessment of Farmgate area using fire risk index, Dhaka City and optimization of fire hydrant placement - Asim Abrar; A.S.M. Maksud Kamal; Abul Kashem Faruki Fahim (Progress in Disaster Science, 2024)
This research addresses fire safety and assesses the vulnerability to fire hazards in the Farmgate area of Dhaka city employing Fire Risk Index (FRI) methodology. 16 key factors were identified from a comprehensive field survey for each building undergoing rigorous analysis for calculation of FRI value through weighting and scoring of each factor. The FRI values are divided into 5 grades of very high, high, moderate, low, and very low with a higher FRI value indicating better fire safety. The data analysis indicates that among all structures, 0.59 % exhibited a very high FRI, 5.35 % showed a high FRI, 17.24 % displayed a moderate FRI, 48.89 % had a low FRI, and 27.93 % had a very low FRI. Geographic Information System (GIS) tools were employed to spatially to optimize fire hydrant placement using data integration and strategic analysis in high-risk areas. By ensuring efficient resource utilization, this research aims to implement fire prevention approaches and serve as a foundational resource for stakeholders, including landowners, residents, and policymakers, to fortify risk awareness and improve overall fire safety protocols. Ultimately, this research aims to foster resilient urban environments, improving disaster preparedness not only in Dhaka but also in similar high-risk areas worldwide.